(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
This study addressed the behavioral problems of individuals with neurodevelopmental disorder, whose behavioral deficits distance them away from the characteristics of what is expected in relation to learning, with losses at a personal, social, academic and professional level. The present narrative review offers a bibliographic survey of the theme, evidencing empirical foundations of applied behavior analysis, whose contributions have been shown to be effective, and the results indicate a decrease in the problem behaviors presented by these individuals. Also, the replacement of these problem behaviors by alternative prosocial behaviors, using the functional analysis methodology. This methodology makes possible to identify the antecedent and consequent events of the problem behaviors and the planning of an appropriate treatment with the use of differential reinforcement.